Method development using chemometric tools for determination of endocrine-disrupting chemicals in bottled mineral waters. (15th February 2022) - Vivas, Mikhael P.M.; Martinez, Sabrina T.; de Andrade, Jailson B.; da Rocha, Gisele O.
Graphical abstract: Highlights: D-μSPE-LC/MS for analysis of EDCs in bottled water was optimized using chemometrics. A method for simultaneous analysis of EDCs in mineral waters is proposed. The proposed D-μ-SPE-LC/MS method was simple, fast, and cost-effective. DMP and BPA were detected at µg L -1 levels in real samples after heat treatment. DMP and BPA's tolerance of daily intake was estimated for adults and children. Abstract: A simple method was developed to determine 14 endocrine-disrupting chemicals (EDCs) in bottled waters, based on dispersive micro-solid phase extraction (d-µ-SPE) and liquid chromatography-mass spectrometry (LC-MS). Extraction was optimized using 2 k-1 factorial and Doehlert experimental designs. Optimized conditions were 80 mg C18, 25 min extraction at 1000 rpm, and 6 min desorption time. Repeatability was below 17 % for all EDCs. LOD and LOQ varied from 1.60 ng L -1 (estradiol, E2) to 23.2 ng L -1 (dimethylphthalate, DMP) and from 5.33 ng L -1 (E2) to 77.3 ng L -1 (DMP). We found DMP and bisphenol A (BPA) in samples after the heat treatment. DMP was up to 58.7 µg L -1, while BPA was up to 1.34 µg L -1 . Tolerance of daily intake (TDI) for DMP were 2.50–2.94 µg kg −1 day −1 (children) and 1.43–1.68 µg kg −1 day −1 (adults). TDI for BPA were 0.03–0.07 µg kg −1 day −1 (children) and 0.01–0.04 µg kg −1 day −1 (adults).